Zapped : a Regan Reilly mystery - Clark, Carol Higgins (New York : Scribner's, 2008)
Returning home from their honeymoon to discover that their neighbor has put his Manhattan apartment up for sale, Regan Reilly and her husband Jack decide to buy it to enlarge their own loft, but the renovation process spawns its own set of problems and an unexpected case.
Keywords: Reilly, Regan (Fictitious character) -- Fiction; Mystery fiction